1982
DOI: 10.1002/art.1780250414
|View full text |Cite
|
Sign up to set email alerts
|

Improving patient cooperation with arthritis treatment regimens

Abstract: This review of the literature on patient cooperation with arthritis treatment recommendations is categorized into 2 sections-involuntary and voluntary lack of cooperation. Extrapolating primarily from investigations of patients with other chronic diseases, 5 stategies for reducing involuntary patient noncooperation and 4 recommendations for improving voluntary patient cooperation are discussed. Although much remains to be learned about factors that influence patient cooperation with arthritis treatment recomme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0
1

Year Published

1984
1984
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 24 publications
(12 reference statements)
0
20
0
1
Order By: Relevance
“…According to Zisook and Gammon (1981), the patient-physician relationship is probably the most significant single factor in determining if a patient will follow the treatment regimen. A body of knowledge reinforces the presumed role of patient-physian trunsuctions in facilitating or inhibiting patient compliance (Buller & Buller, 1987;Christensen, 1978;Davis, 1968;DiMatteo & DiNicola, 1982;Eraker et al, 1984;Greene, Weinberger, Jerin, & Mamilin, 1982;Hulka, Cassell, Kupper, & Burdette, 1976;Jette, 1982;Korsch, Gozzi, & Francis, 1968;Marston, 1970;Sanson-Fisher & Maguire, 1980;Schmidt, 1977;Stewart, 1984). Mechanic (1976) concluded that communication is an essential component of these interpersonal transactions and by implication suggested that there should be a high correlation between satisfaction with physician-patient communication and compliance.…”
Section: Satisfaction and Other Predictors Of Compliancementioning
confidence: 90%
“…According to Zisook and Gammon (1981), the patient-physician relationship is probably the most significant single factor in determining if a patient will follow the treatment regimen. A body of knowledge reinforces the presumed role of patient-physian trunsuctions in facilitating or inhibiting patient compliance (Buller & Buller, 1987;Christensen, 1978;Davis, 1968;DiMatteo & DiNicola, 1982;Eraker et al, 1984;Greene, Weinberger, Jerin, & Mamilin, 1982;Hulka, Cassell, Kupper, & Burdette, 1976;Jette, 1982;Korsch, Gozzi, & Francis, 1968;Marston, 1970;Sanson-Fisher & Maguire, 1980;Schmidt, 1977;Stewart, 1984). Mechanic (1976) concluded that communication is an essential component of these interpersonal transactions and by implication suggested that there should be a high correlation between satisfaction with physician-patient communication and compliance.…”
Section: Satisfaction and Other Predictors Of Compliancementioning
confidence: 90%
“…Jette reported that 45-60% of patients with arthritis do not comply with prescribed exercise programs [2]. More recent studies suggest that it can be as low as 24% [3].…”
Section: Introductionmentioning
confidence: 99%
“…These 'quality' aspects can contribute to the patient's satisfaction with therapy. Any information should be linked to the patient's demands and perceptions, and all regimens should be tailored to the patient's situation and daily routines (Hanson, 1986;Jette, 1982;Lafreniere, 1979;Lazare, Eisenthal, Frank and Stoeckle, 1987;Leventhal and Cameron. 1985).…”
mentioning
confidence: 99%